2003
DOI: 10.2533/000942903777678812
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis of a Pyrazol Analogon of Porphobilinogen with the Help of the Mukaiyama Aldol Reaction

Abstract: The synthesis of a pyrazol analogon of porphobilinogen is described. The Mukaiyama crossed aldol reaction is the key step of our approach. The retrosynthetic analysis follows the mechanism for the biosynthesis of porphobilinogen initially proposed by Shemin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…34 Despite extensive studies, prebiotically plausible conditions have not been identified for the solution dimerization of ALA to give PBG. 35 The lack of a simple route to PBG, while incongruous given the facile occurrence of the seemingly more complex steps 3 and 4 of the pathway, effectively crimps the entire process. The failure to find a viable structure-directed pathway to PBG has been referred to as the ''Achilles' heel'' of the prebiogenesis of tetrapyrrole macrocycles.…”
Section: Introductionmentioning
confidence: 99%
“…34 Despite extensive studies, prebiotically plausible conditions have not been identified for the solution dimerization of ALA to give PBG. 35 The lack of a simple route to PBG, while incongruous given the facile occurrence of the seemingly more complex steps 3 and 4 of the pathway, effectively crimps the entire process. The failure to find a viable structure-directed pathway to PBG has been referred to as the ''Achilles' heel'' of the prebiogenesis of tetrapyrrole macrocycles.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the seemingly complex steps of porphyrinogen formation and subsequent oxidation occur readily under simple conditions. By contrast, examination of earlier steps, namely the formation of porphobilinogen from its universal biosynthetic precursor, ALA, has heretofore failed to identify prebiotically plausible conditions for this deceptively simple dimerization despite extensive studies over the ensuing half-century (for overviews, see Butler and George 1992;Stauffer et al 2001;Chaperon et al 2003). ALA in solution readily undergoes selfcondensation to form the dihydropyrazine and pseudo-porphobilinogen rather than the required porphobilinogen ( Fig.…”
Section: Introductionmentioning
confidence: 94%